Difference in brain activations during appreciating paintings and photographic analogs - Mizokami, Yoshinori; Terao, Takeshi; Hatano, Koji; Hoaki, Nobuhiko; Kohno, Kentaro; Araki, Yasuo; Kodama, Kensuke; Makino, Mayu; Izumi, Toshihiko; Shimomura, Tsuyoshi; Fujiki, Minoru; Kochiyama, Takanori (Frontiers in Human Neuroscience, 2014)
Several studies have investigated neural correlates of aesthetic appreciation for paintings but to date the findings have been heterogeneous. This heterogeneity may be attributed to previous studies’ measurement of aesthetic appreciation of not only the beauty of paintings but also the beauty of motifs of the paintings. In order to better elucidate the beauty of paintings, it seems necessary to compare aesthetic appreciation of paintings and photographic analogues which included corresponding real images. We prepared for famous painters’ pictures and their photographic analogues which were set up to resemble each painting in order to investigate the hypothesis that there exist specific neural correlates associated with the aesthetic appreciation for paintings. Forty-four subjects participated in functional magnetic resonance study which required comparisons of aesthetic appreciation of paintings of still life and landscape versus photographic analogues including corresponding real images of still life and landscape. Bilateral cuneus and the left lingual gyrus were activated in the comparison of aesthetic appreciation of paintings versus photographic analogues. In conclusion, the present findings suggest a possibility of the existence of specific neural correlates associated with the aesthetic appreciation for paintings and that bilateral cuneus and the left lingual gyrus may be involved.